Genetic algorithm-generated SNP barcodes of the mitochondrial D-loop for chronic dialysis susceptibility. (June 2014) - Chen, Jin-Bor; Chuang, Li-Yeh; Lin, Yu-Da; Liou, Chia-Wei; Lin, Tsu-Kung; Lee, Wen-Chin; Cheng, Ben-Chung; Chang, Hsueh-Wei; Yang, Cheng-Hong
Abstract Background and aims: Single nucleotide polymorphism (SNP) interaction analysis can simultaneously evaluate the complex SNP interactions present in complex diseases. However, it is less commonly applied to evaluate the predisposition of chronic dialysis and its computational analysis remains challenging. In this study, we aimed to improve the analysis of SNP–SNP interactions within the mitochondrial D-loop in chronic dialysis. Material & method: The SNP–SNP interactions between 77 reported SNPs within the mitochondrial D-loop in chronic dialysis study were evaluated in terms of SNP barcodes (different SNP combinations with their corresponding genotypes). We propose a genetic algorithm (GA) to generate SNP barcodes. The χ2 values were then calculated by the occurrences of the specific SNP barcodes and their non-specific combinations between cases and controls. Results: Each SNP barcode (2- to 7-SNP) with the highest value in the χ2 test was regarded as the best SNP barcode (11.304 to 23.310; p < 0.001). The best GA-generated SNP barcodes (2- to 7-SNP) were significantly associated with chronic dialysis (odds ratio [OR] = 1.998 to 3.139; p < 0.001). The order of influence for SNPs was the same as the order of their OR values for chronic dialysis in terms of 2- to 7-SNP barcodes. Conclusion: Taken together, we propose an effective algorithm to address the SNP–SNP interactions and demonstrated that many non-significant SNPs within the mitochondrial D-loop may play a role in jointed effects to chronic dialysis susceptibility.